Challenges faced by nurses in complying with aseptic non-touch technique principles during wound care: a review. (12th March 2020) - Sonoiki, Temi; Young, Julie; Alexis, Obrey
Abstract : Background: Surgical and wound site infections (SWSIs) are the second most frequent type of healthcare-associated Infection. One way of preventing SWSIs is by adhering to the principles of asepsis. However, many nurses struggle to apply the principles of aseptic non-touch technique (ANTT) during wound management. Aim: To identify the barriers and enablers that influence nurses' adherence to the principles of ANTT during wound care. Method: A literature search using a systematic approach was carried out. Four databases were searched to identify relevant studies published between January 1993 and December 2018. Titles and abstracts were reviewed. Studies that met the inclusion criteria were reviewed for quality. The extracted data were then synthesised. Findings: A total of seven studies fulfilled the requirements for inclusion. Three themes emerged and were found to be the most dominant factors influencing adherence to the principles of ANTT: material and resources, nurse education, and nurses' behaviour. Conclusion: Nurses' compliance with aseptic practice is directly influenced by environmental and psychological factors. Ensuring compliance to ANTT may require an integrated approach involving local, national and worldwide organisations, in collaboration with higher education institutions that teach nurses and similar healthcare professionals.